Wpływ zanieczyszczenia miedzią i ołowiem gleb okolic Huty Miedzi w Głogowie na zawartość tych pierwiastków w zbożach z okolicznych pól uprawnych = Influence of copper and lead contamination of soils in the Copper Smelter in Głogów locality on the content of these elements in cereals from the surrounding farmland - Rosada, Janusz; Przewocka, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of conducted studies was to determine the content of heavy metals in soils and plants as an indicator of anthropogenic pressure in an agriculture area located in the vicinity of the Copper Smelter GŁOGÓW. The research has identified the content of copper and lead in soils and their impact on spring and winter wheat crops.
Keywords: metale ciężkie; zanieczyszczenia gleb; zanieczyszczenia roślin; pszenica jara; heavy metals; soil pollution; plant contamination; spring wheat